Pengaruh Size dan Sales Growth terhadap Profitabilitas Perusahaan Manufaktur Sektor Konsumsi dengan Struktur Modal sebagai Variabel Moderasi - Wawan Andinata (Diponegoro Journal of Economics, 2021)
This research is motivated by the profitability of companies in the consumer and goods industry sector which have decreased and some have even experienced losses. The main objective of this study is to determine the effect of company size, sales growth on profitability with capital structure as a moderating variable in the industrial sector of goods manufacturing and consumption for the period 2016-2018.The sample of this study consisted of 27 sample companies representing 3 consecutive years. The sampling technique used in this study was purposive sampling, which is a technique with certain considerations or criteria. This research uses Moderating Regression Analysis analysis tools. The results of this study indicate that company size has a negative effect on profitability, sales growth, and capital structure has no effect on profitability. Capital structure is able to moderate company size on profitability and capital structure is unable to moderate sales growth on profitability. The limitation of this research is the low R Square value. Suggestions for future research are to increase the number of independent variables such as the audit committee, extend the research period and add to other manufacturing sectors.